ENSURING THE ECONOMIC SECURITY OF ENTERPRISES - Uktamov Khusniddin (Scholar Express Journals, 2024)
This contribution deals with the financial component that is a key structural element in the system of economic security. The aim of this article is to identify the counterparties of the external environment and certain elements of the internal environment as the main directions in ensuring the financial security of an enterprise. The extraction of the external partners is aimed at identifying potential threats in the financial sphere from the unfair actions of contractors, customers, resource suppliers, buyers of finished products
Keywords: customers; suppliers; extraction; identifying